2021
DOI: 10.1177/0193945920988785
|View full text |Cite
|
Sign up to set email alerts
|

Health Promotion Behaviors among Urban Black Women

Abstract: Health-promotion behaviors among urban Black women are the forefront of US health policy regarding health disparities. This cross-sectional study explored factors such as health literacy, self-efficacy, and readiness for change with health-promotion behaviors of urban Black women. Although these variables are relevant, urban Black women have identified that spirituality and history of domestic violence were also relevant. The sample consists of 152 participants from outpatient clinics, community events, and gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…In a study of Taiwan adolescents found that adolescents with high and low HL did not significantly differ with some health promoting behaviors ( 41 ). The lack of a statistically significant relationship between HL and health promotion behaviors was also found in a study of urban black women in the United States ( 42 ). More importantly, in a study on training and counseling interventions provided by public health nurses during home visits, participants' health lifestyles did not improve when their HL increased ( 43 ).…”
Section: Discussionmentioning
confidence: 58%
“…In a study of Taiwan adolescents found that adolescents with high and low HL did not significantly differ with some health promoting behaviors ( 41 ). The lack of a statistically significant relationship between HL and health promotion behaviors was also found in a study of urban black women in the United States ( 42 ). More importantly, in a study on training and counseling interventions provided by public health nurses during home visits, participants' health lifestyles did not improve when their HL increased ( 43 ).…”
Section: Discussionmentioning
confidence: 58%
“…Many previous studies have been conducted to investigate the level of health promotion behaviors among older adults [5,[7][8][9][10]. However, most of them focused on urban older adults [7,8], or analyzed urban and rural residents as a group, without taking into account differences in where they lived [5,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Many previous studies have been conducted to investigate the level of health promotion behaviors among older adults [5,[7][8][9][10]. However, most of them focused on urban older adults [7,8], or analyzed urban and rural residents as a group, without taking into account differences in where they lived [5,9,10]. Several studies have shown that the level of health promotion behaviors among older adults is affected by the living area [5,9,10].…”
Section: Introductionmentioning
confidence: 99%